2007
DOI: 10.1529/biophysj.107.109728
|View full text |Cite
|
Sign up to set email alerts
|

Rows of ATP Synthase Dimers in Native Mitochondrial Inner Membranes

Abstract: The ATP synthase is a nanometric rotary machine that uses a transmembrane electrochemical gradient to form ATP. The structures of most components of the ATP synthase are known, and their organization has been elucidated. However, the supramolecular assembly of ATP synthases in biological membranes remains unknown. Here we show with submolecular resolution the organization of ATP synthases in the yeast mitochondrial inner membranes. The atomic force microscopy images we have obtained show how these molecules fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 49 publications
(53 reference statements)
6
64
1
Order By: Relevance
“…IF1 Does Not Affect Mitochondria Morphology-Previous studies reported that knockdown of IF1 caused stimulation of autophagy, decrease in mitochondrial volume fraction in the cell, and decrease in cristae density in mitochondria (10,11,13,14). However, none of these were observed for IF1-KD cells with certainty in our study.…”
Section: Discussionsupporting
confidence: 44%
“…IF1 Does Not Affect Mitochondria Morphology-Previous studies reported that knockdown of IF1 caused stimulation of autophagy, decrease in mitochondrial volume fraction in the cell, and decrease in cristae density in mitochondria (10,11,13,14). However, none of these were observed for IF1-KD cells with certainty in our study.…”
Section: Discussionsupporting
confidence: 44%
“…Ref. 19) and suggests that the sense of rotation of F-ATPase influences the mCrC of Drosophila mitochondria, possibly by modulating accessibility of Ca 2ϩ -sensitive site(s) that trigger channel opening (20).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the association of ATP synthases in the mitochondrial membrane was evidenced from chemical cross-linking (15,16) and in vivo cross-linking experiments (17). More recently, atomic force microscopy and electron microscopy experiments revealed the oligomeric state of the enzyme in the inner mitochondrial membrane of yeast (12,18) and the presence of dimer ribbons of ATP synthase in mammalian mitochondria (19) and Polytomella mitochondria (20). Rows of F 1 were also observed by cryo-electron tomography of Neurospora crassa mitochondria (21).…”
mentioning
confidence: 98%